Persilangan Kultural dalam Mengelola Keberagaman Pada Masyarakat Muslim-Kristen Siringo-Ringo Sumatera Utara - Nurus Shalihin; Dina Sari Hasibuan; M. Yusuf; Muliono Muliono (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2021)
This study aims to explore the potential for diversity in Siringo-Ringo Village to become a role model in the practice of managing diversity in Indonesia. The potential for diversity in Siringo-Ringo is portrayed by the diversity of religion, ethnicity, being and profession of civil society. With a descriptive qualitative research approach and data collection techniques using in-depth interviews, this study answered two questions; first, what is the potential for diversity in the Siringo-Ringo people that makes Muslim and Christian communities live in harmony. Second, how is the institutionalization of diversity in the Siringo-Ringo community between Muslim and Christian communities? This study finds that diversity that experiences crossover (adherents of religion, practice of religious space and economics) is a natural strategy that can create harmony in the midst of diversity. Then, with the institutionalization (married, death and religious holidays) that are cultural in nature, it is able to become a medium for bringing together existing crosses. This study concludes that cross relations can create conditions of harmony, tolerance, inclusion and harmony between various differences.